2014
DOI: 10.3389/fimmu.2014.00258
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Natural Killer Cells and CD8+ T Cells in Hepatitis B Virus Infection

Abstract: Hepatitis B virus (HBV) infection is one of the main causes of chronic liver diseases that may progress to liver cirrhosis and hepatocellular carcinoma. Host immune responses are important factors that determine whether HBV infection is cleared or persists. Natural killer (NK) cells represent the main effector population of the innate immune system and are abundant in the human liver. Recently, it has been demonstrated that NK cells not only exhibit antiviral functions but may also regulate adaptive immune res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
57
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 107 publications
(137 reference statements)
0
57
0
1
Order By: Relevance
“…In addition, chimpanzees inoculated with ∼5 3 10 7 GE HBV DNA showed that noncytopathic antiviral mechanisms contributed to HBV clearance, possibly via NK cells (39), suggesting that high HBV doses might induce the noncytopathic antiviral mechanisms of NK cells mediating HBV clearance. Other studies, however, have indicated that high viral load may be associated with a reduction of noncytolytic NK cell responses (48,51). In our model, we show that the primary role of NK cells is to induce anti-HBV CD8 + T cell responses rather than to exert direct antiviral activity.…”
mentioning
confidence: 47%
“…In addition, chimpanzees inoculated with ∼5 3 10 7 GE HBV DNA showed that noncytopathic antiviral mechanisms contributed to HBV clearance, possibly via NK cells (39), suggesting that high HBV doses might induce the noncytopathic antiviral mechanisms of NK cells mediating HBV clearance. Other studies, however, have indicated that high viral load may be associated with a reduction of noncytolytic NK cell responses (48,51). In our model, we show that the primary role of NK cells is to induce anti-HBV CD8 + T cell responses rather than to exert direct antiviral activity.…”
mentioning
confidence: 47%
“…In contrast, CHB infection is characterized by an exhausted phenotype of specific T cells, possibly because of (i) strong and long‐term exposure to secreted HBV antigens (ie APC‐induced T‐cell suppression), (ii) overall lack of activation of innate immune cells and deficient antigen presentation by infected cells and (iii) a highly tolerogenic environment in the infected liver because of over representation of immune‐modulatory cells and secretion of tolerogenic molecules (Figure ) . Interestingly, it has also been shown that the function and cross‐talk of other cell types, including NK/NKT dendritic cells are impaired during CHB, contributing to the overall lack of efficient immune response against the virus …”
Section: Immune System Manipulationmentioning
confidence: 99%
“…Many research groups have shown that NK cells in patients with chronic hepatitis B become defective in terms of producing IFN-c with preserved cytotoxic activity [31][32][33][34][35]. Furthermore, TRAIL (TNF-related apoptosis-inducing ligand)-expressing NK cells eliminate HBV-specific T cells which highly express the TRAIL death receptor TRAIL-R2 [36].…”
Section: Nk Cells and Dcs In Chronic Hbv Infectionmentioning
confidence: 99%